Ototoxic effect of Burow solution applied to the guinea pig middle ear - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Objective: To analyze the ototoxicity of Burow solution as an otologic preparation. Background: Burow solution has been used for years in the treatment of acute or chronic otitis externa and chronic suppurative otitis media. This acidic solution has antibacterial and antiedematous properties. Ototoxic effect of Burow solution has not been known, so the current study was designed to observe the ototoxic effect of Burow solution experimentally. Materials and Methods: Experiments were performed in 32 young, male albino guinea pigs (weight, 450-550 g). Twenty animals in the experimental group were divided into 2 groups of 10 animals each. The first group received 13% Burow solution (13% aluminum subacetate), and the second received 4% Burow solution (4% aluminum subacetate). Twelve animals in the control group were divided into 2 groups of 6 animals each. The first group received gentamicin (40 mg/mL; ototoxic control), and the second received saline solution (negative control). Under general anesthesia, pretreatment auditory brainstem responses (ABRs) from the right ear were obtained from the animals in all groups. The right tympanic membranes were widely perforated, and a small piece of Gelfoam was applied to the middle ear. Ear solutions at concentrations of 0.1 mL were applied through transcanal approach to the middle ear twice a day in 10 days. Under general anesthesia, the Gelfoam was removed from the right middle ear, and posttreatment ABRs were obtained 14 days later after the initial time in all groups. Results: Baseline ABR results were normal in right ears of all animals tested. Animals undergoing placement of Gelfoam with either 13% Burow solution, 4% Burow solution, or saline in the middle ear showed no changes in ABR threshold. The gentamicin group showed significant change in the ABR threshold. Conclusion: Burow solution was considered to be an effective and safe otologic preparation.
Keywords: burow solution; ear drop ototoxicity; auditory brainstern responses; SUPPURATIVE OTITIS-MEDIA; INFECTIONS; DILUTION